The Metaphor of Life: Meaning Analysis for Clearly Understanding of Life - Puchthonglang, Prateep (วารสารสันติศึกษาปริทรรศน์ มจร, 2017)
The metaphor is the method and teaching technique used by the Buddha most frequently to describe the abstract as concrete. Comparing issues clarify that the listener understand clearly without the need for more explanation. The metaphor in Sutra shown by the Lord Buddha was plentiful. There had aims, sharp and usefulness that making the subject incomprehensible becomes easy to understand. This qualitative research paper aims to present the study and meaning analysis of the metaphor of life in Suttanta Pitaka. The findings indicated that Suttanta Pitaka had 32 the metaphors of life i.e. Life is like a knife cut into the water. When you raise your hand, it disappears, Life is like a boil boom, Life is like a canary but it's not real Life is like a leather bag etc. Lord Buddha, Bodhisattva, Vedas and His Disciples had teached for the clearly understanding of life according to Anicca, Dukkha, Anatta and Asupa will lead to the correct practice of Buddhism.